USE of Genitic Algorithm and Particle Swarm Optimisation Methods for the Optimal Control of the Reactive Power in Western Algerian Power System - Naima, Kalfallah; Fadela, Benzergua; Imene, Cherki; Abdelkader, Chaker (Energy procedia, 2015)
This paper describes the methodology adopted for controlling the reactive power in western Algerian power system. This Algerian system is in phase of extension because of the strong increase of the request of electricity (+ 5 in 7% a year), With a population increasing by 1.2% a year, and which changes these consumer habits using a large number of modern electrical equipments. Our objective is to study this system and to try to solve these problems by the optimization of the reactive powers through Felexible AC Transmission System devices and metaheuristics methods of optimization. Several metaheuristics algorithms have been developed based on Genetic Algorithm approach and the swarm intelligence. Those algorithms try to prove their effectiveness in minimizing the power losses, subject to satisfying system constraints like voltage levels, real and reactive power flow on transmission lines, transformer tap settings and switching of discrete portions of inductors or capacitors.